The design of a randomized controlled trial to evaluate multi-dimensional effects of a section 1115 Medicaid demonstration waiver with community engagement requirements - Linn, Kristin A. (Contemp Clin Trials, 2020)
Section 1115 demonstration waivers provide a mechanism for states to implement changes to their Medicaid programs. While such waivers are mandated to include evaluations of their impact, randomization – the gold standard for assessing causality – has not typically been a consideration. In a critical departure, the Commonwealth of Kentucky opted to pursue a two-arm randomized controlled trial (RCT) for their controversial 2018 Medicaid Demonstration waiver, which included work requirements as a condition for the subset of beneficiaries deemed able-bodied to maintain eligibility for benefits. Beneficiaries were randomized 9:1 to the new waiver program or a control group who would retain their current benefits as part of the existing Medicaid expansion program. To address potential bias from differential attrition from the Medicaid program that would accrue from solely analyzing administrative data, our team designed a rich, prospective, longitudinal survey to collect primary and secondary outcomes from six categories of interest to policymakers: insurance coverage, health care utilization and quality, health behaviors, socioeconomic measures, personal finances, and health outcomes. At baseline, a subset of survey participants was invited to participate in the collection of biometric samples via in-person follow-up visits, and a cross-section were also invited to participate in qualitative interviews. While the demonstration waiver was terminated before the program began, our study design illustrates that it is possible for other researchers and state agencies seeking to evaluate Medicaid demonstration waivers and other demonstration policies to work together to implement high quality randomized trials – even for controversial policies.